(3GdPNGFQ hGdJMa heG cGf HGdbUQ ef Pdcs - (3CMeO Hf YHO Gddg Hf GdMSf Hf WhZGf GdChMOj GdebQF GdTGaYj,J (B811 (3g` s ((3UGQe GdOjf EHQGgje Hf eMeO Hf BjOeQ Hf ObeGb GdbGgQi s)
(3ChdgG (B:s
(3gPG cJGH ajg PcQ GdgOGjG hGdJMa GdYXjeI GdCbOGQ hGdfabGJ ai GdhdGFe hGdOYhGJ hGdPNGFQ GdeUhfGJ heG CaQL ef NRGFf bUQ GdEeGe GdeSJfUQ HGddg ai CjGe GdaJfI s
(3BNQgG (B:s
(3abGd eGgi HjVI fYGeI hdcf gi HjVI MjI cGf HYV Gdedhc CgOGgG Edi LOi GdbGFe HCeQ Gddg hgPg GdQbYI HNW GdbGFe HCeQ Gddg HGSe egOjgG hGdSfI GdJi GgOjJ ajgG gPG BNQ eG GNJQfGg eeG hLO ef cJGH GdgOGjG hGdJMa s
(3GdMb HGdfSNI HebOGQ hQbI RjGOGJ Ydi eG hLO ef cJGH GdgOGjG hGdJMa GNJGQgG UGMHfG GdGejQ TgGH GdOjs
(3UOQ gPG GdcJGH ai GdchjJ eMbbkG hefShHkG Edi GdbGVi GdQTjO GdRHjQ GdeJhai SfI (B563 (3hJYbH gPg GdfSHI HYV GdHGMKjf hTcchG ai UMJgGs
(3cJHJ GdfSNI Hbde ajg VHWs
(3JHUQI GdYfhGf (B:s
(3GNJjGQ s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs